Hybrid Design of Optimal Capacitor Placement and Reconfiguration for Performance Improvement in a Radial Distribution System - Ali Nasser Hussain; Waleed Khalid Shakir Al-Jubori; Haider Fathi Kadom (Journal of Engineering)
Distribution System Reconfiguration (DSR) and Optimal Capacitor Placement (OCP) are the most alternative techniques for increasing the power system generation and covering the growth of power demands. These techniques reduce the Radial Distribution System (RDS) losses and enhance the voltage profile. Combining both techniques gives better performance than using the individual technique. In this paper, two operation modes were implemented. First, the individual mode of OCP is applied. Second, the dual mode of DSR after OCP process is applied. Multiobjective functions with considering the weighting factors are used for minimizing real losses, improving voltage profile, and increasing saving cost. The optimal selections of open switches, location, and size of capacitors in the individual and dual design for RDS are achieved using four different optimization algorithms. These algorithms are Modified Biogeography-Based Optimization (MBBO) algorithm, Cuckoo Search (CS) algorithm, Modified Imperialist Competitive (MIC) algorithm, and Modified Bacterial Foraging-Based Optimization (MBFBO) algorithm. These algorithms are applied for two standard networks (IEEE 33- and IEEE 69-bus). Comparisons among the proposed algorithms are done, and the results demonstrated that the MBBO algorithm is the most strong and fast algorithm to attain the optimum solution. In addition, comparisons with literature works are done to validate the effectiveness of proposed algorithms.